The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.1023/a:1008801802877
|View full text |Cite
|
Sign up to set email alerts
|

The proxy problem: child report versus parent report in health-related quality of life research

Abstract: This study evaluates the agreement between child and parent reports on children's health-related quality of life (HRQoL) in a representative sample of 1,105 Dutch children (age 8-11 years old). Both children and their parents completed a 56 item questionnaire (TACQOL). The questionnaire contains seven eight-item scales: physical complaints, motor functioning, autonomy, cognitive functioning, social functioning, positive emotions and negative emotions. The Pearson correlations between the child and parent repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
243
3
3

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 577 publications
(273 citation statements)
references
References 23 publications
24
243
3
3
Order By: Relevance
“…Parents reported a lower HRQOL in older children with PWS, while this was not reported by the children. Disagreement between parent and child reports on HRQOL was found in other studies in children with other disorders than PWS [12,14]. Parents may score lower because they are negatively influenced by the burden of care-giving, their own well-being, and concerns about their child's future perspectives [32,33], and children might be positively influenced by adaptation to their illness [34].…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Parents reported a lower HRQOL in older children with PWS, while this was not reported by the children. Disagreement between parent and child reports on HRQOL was found in other studies in children with other disorders than PWS [12,14]. Parents may score lower because they are negatively influenced by the burden of care-giving, their own well-being, and concerns about their child's future perspectives [32,33], and children might be positively influenced by adaptation to their illness [34].…”
Section: Discussionmentioning
confidence: 86%
“…However, as parents are generally quite able to determine their child's HRQOL, a combination of child reports and parent reports seems to be most useful [12,13,14]. …”
Section: Introductionmentioning
confidence: 99%
“…This complementary use of self-reports and proxy reports is not a minor issue for the operationalization of a developmental approach to pedopsychiatric QL assessment. Although parents' reports and their children's QL reports are valid, they cannot effectively supplant each other [104]. From this perspective, the complexity and costs related to this methodological option are surpassed by a number of advantages and applications.…”
Section: Discussionmentioning
confidence: 99%
“…Differences in proxy agreement at the individual child-parent level have been described for the generic TACQOL [32,33]. It has been indicated that children report less consistent and are more influenced by single experiences, while parents give information based on more structured and general observations [18].…”
Section: Discussionmentioning
confidence: 99%